Optimization of weight ratios of the components in polyaniline based composites on the basis of their electrochemical performances - Das T.; Verma B. (My University, 2025)
Ternary composites of polyaniline-acetylene black-manganese cobaltite were synthesized with different weight ratios. The optimized weight ratio of aniline, acetylene black, manganese cobaltite is found to be 4:1:2 (PAMC1) based on electrochemical performances. PAMC1 based two-electrode cell had the highest specific capacitance of 264 Fg−1 at 1 mA. PAMC1 has the highest coulombic efficiency of 99.41%. PAMC1 has the highest specific energy and power of 23.47 Wh kg−1 and 102.91 W kg−1 at 1 mA. Capacitance retention of PAMC1 after 5000 cycles is 90%. PAMC1 has a reasonably low charge transfer resistance of 2 Ω. © 2021 Taylor & Francis Group, LLC.